Design And Development Of Internet Of Things (IoT) Based System For Monitoring Energy Consumption - Anuar, Muhamad Shafiq (Universiti Sains Malaysia, 2022)
The Internet of Things (IoT) is a highly advanced technology that may be utilised for various applications that benefit human existence. Currently, with the growth of technology, electricity consumption is relatively high. To prevent the waste of electrical energy, we must monitor and regulate this energy so that no waste occurs. Since more electrical equipment is used in the home nowadays, we conducted experiments in the home to monitor and manage the electrical energy used so that it is not squandered excessively. We, therefore, design and develop an Internet of Things (IoT) based system for monitoring residential energy consumption. The design's primary components are the ESP8266 microcontroller, SCT013-000 current sensor, motion sensor, and relay. The measurement reading accuracy was acceptable, with an error of less than 5%. In this experiment, the electrical appliances fall into two categories: scheduled and unscheduled load, and data is collected for two months, April and May. After applying an energy home system to a scheduled load, we can see that May's energy consumption is substantially lower than April's, which is 0.9130KWh and 1.5332KWh, respectively. In addition, the housing was designed to accommodate every electrical component, and stress analysis was conduct.